Hemodialysis Patient Safety Instruments: A Systematic Review - Anwar, Choirul (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2024)
Hemodialysis is a technically complex procedure with many potential adverse events that can harm patients when they occur. However, hemodialysis services have not been fully implemented in standard operating procedures such as the administration process or hemodialysis programming, resulting in discomfort, adverse events, and the possibility of mild to severe patient incidents. This study aimed to review and criticize various instruments that discuss research and development of instruments to prevent adverse events in hemodialysis services. Articles from 2013 to 2023 were chosen from Scopus, Pubmed, ScienceDirect, and Web of Science. The terms used were hemodialysis safety, hemodialysis patient safety, and hemodialysis patient safety instrument based on paper, website, and technology. Overall, the review consists of 12 articles. This review discusses strategies for developing innovation, technology, or patient safety instruments and reporting to reduce adverse events and improve patient safety. The development of patient safety instruments can reduce adverse events and improve patient safety so that it can impact the aspects of improving the quality of service of a health care institution, especially hemodialysis services.  Keywords: Dialysis patient safety instrument, Hemodialysis, Hemodialysis patient safety instrument.